2013
DOI: 10.1016/j.pmrj.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Ultrasound‐Guided Platelet‐Rich Plasma Injections for Chronic Tendinopathy: A Multicenter, Retrospective Review

Abstract: In this retrospective study, in which we evaluated administration of PRP for chronic tendinopathy, we found that the majority of patients reported a moderate (>50%) improvement in pain symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 30 publications
3
101
0
1
Order By: Relevance
“…The follow-up in those studies lasted 24 weeks and 28 months respectively. As for Achilles tendinopathy, several other studies also demonstrated a decrease in pain following a PRP injection [15][16][17]. To the authors' opinion, the lack of significant results in the tendon-specific part of the present study is therefore due to the small number of patients recruited.…”
Section: Are There Biologic Factors Of Good Prognosis After a Platelementioning
confidence: 58%
“…The follow-up in those studies lasted 24 weeks and 28 months respectively. As for Achilles tendinopathy, several other studies also demonstrated a decrease in pain following a PRP injection [15][16][17]. To the authors' opinion, the lack of significant results in the tendon-specific part of the present study is therefore due to the small number of patients recruited.…”
Section: Are There Biologic Factors Of Good Prognosis After a Platelementioning
confidence: 58%
“…In the multi-center, retrospective study by Mautner et al [50], the patellar tendon was found to be the most difficult to treat, with greater than 50 % or more improvement noted in only 59 % of patients treated for chronic patellar tendinopathy.…”
Section: Patellar Tendonmentioning
confidence: 99%
“…In a retrospective cross-sectional survey, Mautner et al [50] assessed the results of 325 patients who received ultrasound-guided PRP injections for tendinopathy that was refractory to conventional management. Only 180 patients that were contacted answered the survey.…”
Section: Multi-tendon Tendinopathy Studiesmentioning
confidence: 99%
“…On clinical examination, there is often palpable tenderness and pain over the ischial tuberosity against resisted knee flexion. Furthermore, active stretching of the hamstrings recreates the pain at the site of the ischial © C I C E d i z i o n i I n t e r n a z i o n a l i plasma (PRP) injection 19,[23][24][25]38,39 . When compared to a combined NSAID, physiotherapy and a hamstring specific exercise program, SWT had significantly better results with a mean follow-up of 10.7 months 19 .…”
Section: Clinical Presentationmentioning
confidence: 99%